KETIKA COVID -19 MENYERBU TAMAN DIDASKALOS - Yonas Muanley (JURNAL LUXNOS, 2020)
Abstract: This study aims to reveal the negative and positive sides of the spread of Covid-19 which does not rule out the possibility of entering the theological high school campus which in this article uses a theological technical term, namely taman didaskalos. Taman didaskalos is a technical term used to refer to the place where the activities of didaskalos (teachers / lecturers and prospective teachers) take place, namely the Theology College campus, especially the Santosa Asih IKSM Theological College. The method used is a qualitative research method using domain taxonomic data analysis. The theory used is the study of Covid-19 and didaskalos which is based on a number of theoretical-theological truths about the two concepts studied, namely Covid and Didaskalos. The findings were that the didaskalos, especially the didaskalos candidates, saw Covid Covid-19 as an enemy, while Covid-19 as a friend still needed deep thinking about Covid-19. Keywords: Covid-19, Taman, Didaskalos Abstrak: Penelitian ini bertujuan untuk mengungkapkan sisi negative dan positif dari penyebaran Covid-19 yang tidak menutup kemungkinan dapat memasuki kampus sekolah tinggi teologi yang di dalam artikel ini menggunakan istilah teknis teologis yakni taman didaskalos. Taman didaskalos adalah istilah teknis yang dipakai untuk merujuk pada tempat berlangsungnya kegiatan para didaskalos (guru/dosen dan calon guru) yaitu kampus Sekolah Tinggi Teologi khususnya Sekolah Tinggi Teologi IKSM Santosa Asih. Metode yang dipakai yakni metode penelitian kualitatif dengan menggunakan analisis data taksonomi domain. Teori yang digunakan yakni kajian tentang Covid-19 dan didaskalos yang didasarkan pada sejumlah kebenaran teoritik-teologis tentang dua konsep yang diteliti yaitu Covid dan didaskalos. Temuannya yakni para didaskalos khususnya calon didaskalos memandang Covid Covid-19 sebagai musuh, sementara Covid-19 sebagai kawan masih memerlukan pemikiran yang mendalam tentang Covid-19. Kata Kunci: Covid-19, Taman, Didaskalos